PENERAPAN DATA MINING UNTUK MENGANALISA POLA PERMINTAAN PEMASANGAN CCTV DENGAN MENGGUNAKAN METODE MARKET BASKET ANALYSIS STUDY KASUS CV. MITRA JAYA PERKASA - Ramadhan Pandapotan Siringo–Ringo; Melda Panjaitan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
CV. MITRA JAYA PERKASA is a company engaged in CCTV installation services where demand for CCTV installation is one of the important factors. Therefore it is very important to know the cctv installation request pattern so that it can adjust to the warehouse stock and the cctv goods linkage. With the help of computers can be used as a solution to the problem, where by building a data mining system which is a knowledge-based computer program that provides solutions to problems and get information from large data warehouses. In this case the company can analyze the cctv installation request pattern using the market basket analysis method. It is expected that this data mining can provide information on the cctv installation request pattern and adjust the warehouse stock. The results of this study are an application that can help analyze the cctv installation request patterns and analyze the relationship of goods using the market basket analysis method.Keywords: Data Mining, Market Basket Analysis, cctv installation request patterns.